Retrograde Cricopharyngeus Dysfunction effectively treated with low dose botulinum toxin. A case report from Italy - Pavesi, Luca; Balzano, Cecilia; Mauramati, Simone; Giudice, Carla; Fresia, Mauro; Todisco, Massimiliano; Alfonsi, Enrico; Cosentino, Giuseppe (Frontiers in Neurology, 2023)
A large constellation of hitherto unexplained symptoms including inability to burp, gurgling noises from the chest and lower neck, abdominal bloating, flatulence, painful hiccups and emetophobia was defined as Retrograde Cricopharyngeus Dysfunction (R-CPD) in 2019. First choice treatment of R-CPD involves injection of botulinum toxin into the cricopharyngeus muscle under local or general anesthesia. This treatment has been found to be effective in the vast majority of subjects, with limited adverse events and prolonged therapeutic effects. Notwithstanding, R-CPD is still a poorly understood and underestimated disease, and a specific therapeutic dosage range of botulinum toxin (BT) has not been yet established. In this report, we describe the first case of R-CPD diagnosed in Italy, successfully treated with unilateral, anesthesia-free injection of 10 units of onabotulinum toxin into the cricopharyngeus muscle, representing the lowest dose reported to date.